2010
DOI: 10.1016/j.biochi.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Translation factor LepA contributes to tellurite resistance in Escherichia coli but plays no apparent role in the fidelity of protein synthesis

Abstract: LepA is a translational GTPase highly conserved in bacterial lineages. While it has been shown that LepA can catalyze reverse ribosomal translocation in vitro, the role of LepA in the cell remains unclear. Here, we show that deletion of the lepA gene (ΔlepA) in E. coli causes hypersensitivity to potassium tellurite and penicillin G, but has no appreciable effect on growth under many other conditions. ΔlepA does not increase miscoding or frameshifting errors under normal or stress conditions, indicating that Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 49 publications
3
57
1
Order By: Relevance
“…Second, direct measurements of translation elongation using a pulse-chase method showed that LepA has no effect on the rate (4). Third, the frequencies of miscoding, spontaneous +1 and -1 frame-shifting, and programmed +1 frame-shifting are indistinguishable in wild-type and ΔlepA cells (7). Thus, the simplest interpretation of the ribosome profiling data is that LepA contributes primarily to the initiation phase of translation in the cell.…”
mentioning
confidence: 99%
“…Second, direct measurements of translation elongation using a pulse-chase method showed that LepA has no effect on the rate (4). Third, the frequencies of miscoding, spontaneous +1 and -1 frame-shifting, and programmed +1 frame-shifting are indistinguishable in wild-type and ΔlepA cells (7). Thus, the simplest interpretation of the ribosome profiling data is that LepA contributes primarily to the initiation phase of translation in the cell.…”
mentioning
confidence: 99%
“…Although EF4 is highly conserved in bacteria (4), deletion of ef4 gene causes no evident phenotype in Escherichia coli under optimal growth conditions (6). However, EF4 was shown to notably improve protein synthesis under stress conditions (7).…”
mentioning
confidence: 99%
“…For example, wild-type (fully modified) ribosomes seem to depend on BipA for translation of specific mRNAs (11). Furthermore, as with EF4, overexpression of BipA inhibits transfer-messenger mRNA (tmRNA)-dependent peptide tagging activity of nonstop messages on ribosome (6). Thus, BipA likely functions as an elongation factor as well.…”
mentioning
confidence: 99%
“…30 The extreme conservation across phyla is 'paradoxically associated with an apparent lack of phenotype in deletion mutants'. 31 For example, while E. coli cells lacking the EF4 gene have no ostensible defects in cell growth or protein export under normal medium and temperature, they show defective growth under stress conditions 32 (see below). Similarly, EF4 is one of the 10 genes essential to the survival of Helicobacter pylori in low pH environment.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results suggest that EF4 is essential in conditions that counteract faithful protein synthesis such as upon exposure to magnesium salts 36 and potassium tellurite. 32 In these suboptimal environments, Guf1/LepA activity remobilizes stuck ribosomes and transiently inhibits the elongation process to optimize protein synthesis. 36,37 We therefore assessed complementation on plates supplemented with potassium tellurite, magnesium or low levels of chloramphenicol.…”
Section: Resultsmentioning
confidence: 99%